ANALISIS PENERAPAN ACTIVITY BASED COSTING DAN TARGET COSTING DALAM MENINGKATKAN LABA DENGAN JUST IN TIME SEBAGAI VARIABEL MODERATING PADA BERKAH JAYA MANDIRI SURABAYA - Nurhayati, Dewi; Abiantoro, Bayu; Laisoka, Duvan Samudra; Fiorentino, Kevin; Riyadi, Slamet; Pandin, Maria Yovita R (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
In the era of globalization with rapid advances in information technology, various lines of manufacturing industry, both old and new, are increasingly developing. The business environment continues to change and develop. This research aims to see the influence of Activity Based Costing on profits, see the influence of Target Costing on profits partially, the influence of profits on Just In Time (JIT) partially, and see the influence of Activity Based Costing, Target Costing, on profits with Just In Time as a moderating variable at Berkah Mandiri Jaya, Surabaya. This research uses quantitative methods with statistical analysis to process data in the form of numbers. The findings discover that the application of the Activity Based Costing method can increase company profits. This is because the method provides accurate cost information and enables precise pricing for each product.